Ecology for Whom? Deep Ecology and the Death of Anthropocentrism - Ferrer Montaño, Orlando José (Opción, 1970)
Deep Ecology arises as a new perception to visualize the inexorable changes that humanity currently confronts. This new scientificphilosophical-religious approach claims for a new treatment for the Earth. However, this new eco-centered approach transcends the limit of any particular science of today, and claims that simple reforms are not sufficient. Deep Ecology calls for a reduction of human population and change to our high-energy consumption and profligate resource use. Anthropocentrism should be substituted by ecocentrism; a shift from anthropos, the human, to eco, the Earth. Although I amnot an advocated to Deep Ecology, in this paper I present a series of thoughts endorsing some of the Deep Ecology”™s claims. I argue that deep ecological thinking and actions, together with a better use of our scientific, economic and natural resources will add for a better and lasting global world.